Virtualna resničnost kot pripomoček pri poučevanju religijskih vsebin v šolah - Jeglič, Urška (Bogoslovni vestnik, 2024)
This article presents the results of a survey conducted as part of the Erasmus+ project VR4Empathy. The aim of this survey was to find out how well secondary school students and teachers know virtual reality and where they see its use in the classroom. The realisation that religious and ethical content was not mentioned in the survey prompted us to write this article in which we try to shed light on the state of religious education in Slovenia and present virtual reality as a tool for teachers and students to learn this type of content.
Keywords: education; izobraževanje; modernisation of the learning system; posodobitev učnega sistema; pouk religij; religious education; virtual reality and religious education; virtual reality in schools; virtualna resničnost in religijski pouk; virtualna resničnost v šoli